2020
DOI: 10.3390/ijerph17217998
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emotional Intelligence and Psychosocial Risks on Burnout, Job Satisfaction, and Nurses’ Health during the COVID-19 Pandemic

Abstract: Nurses are exposed to psychosocial risks that can affect both psychological and physical health through stress. Prolonged stress at work can lead to burnout syndrome. An essential protective factor against psychosocial risks is emotional intelligence, which has been related to physical and psychological health, job satisfaction, increased job commitment, and burnout reduction. The present study aimed to analyze the effect of psychosocial risks and emotional intelligence on nurses’ health, well-being, burnout l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
141
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 196 publications
(170 citation statements)
references
References 60 publications
10
141
0
19
Order By: Relevance
“…Open access very experienced, having worked in the NHS for many years and have previously reported higher levels of job satisfaction and well-being than other areas of the NHS. 19 Increased fear due to the pandemic has been associated with higher levels of burnout in Spain, 22 decreased psychological well-being in the USA 23 and higher intention to leave in the Philippines. 24 Studies in China and Iran have already shown that healthcare staff who are not properly equipped in this crisis are at high risk of mental health conditions such as depression, anxiety and post-traumatic stress disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Open access very experienced, having worked in the NHS for many years and have previously reported higher levels of job satisfaction and well-being than other areas of the NHS. 19 Increased fear due to the pandemic has been associated with higher levels of burnout in Spain, 22 decreased psychological well-being in the USA 23 and higher intention to leave in the Philippines. 24 Studies in China and Iran have already shown that healthcare staff who are not properly equipped in this crisis are at high risk of mental health conditions such as depression, anxiety and post-traumatic stress disorder.…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto a los trabajos que han puesto en relación la IE con la satisfacción laboral y salud, apuntan en términos generales que la IE se relaciona positivamente con la salud y satisfacción laboral y negativamente con el estrés/ burnout. Así, en el contexto de la enfermería contamos con trabajos que encuentran relaciones positivas entre IE y satisfacción laboral y sugieren que la IE puede mejorar la salud general, satisfacción laboral y disminuir el agotamiento de este colectivo (Cummings et al, 2005;Powell et al, 2015;Soto-Rubio et al, 2020).…”
Section: El Papel De La Ie En Profesionales De Enfermeríaunclassified
“…To conclude, it should be noted that for the reasons previously stated, studies such as this one are relevant and necessary, even more so in the current context marked by the health emergency caused by COVID-19 [ 73 , 74 , 75 ]. The current pandemic accentuates the critical situations with which all health professionals, including anesthesiologists, have to work, and any effort to care for them is needed now more than ever.…”
Section: Resultsmentioning
confidence: 99%
“…However, while it is true that the profile of burnout in anesthesiologists in Poland may have varied over the years, we believe that the way in which the variables relate to each other remains valid and relevant in studying how guilt is related to burnout and the development of depression and health problems. Although it is true that in 2020 the situation at the health level has changed substantially because of the pandemic caused by COVID-19, we considered that precisely knowing how guilt is related to burnout, depression, and health of health professionals can be of crucial importance in order to care for these professionals at the time they need it most, because we believe that the pandemic will have greatly increased the stressors they face in their daily work [ 73 , 74 , 75 ].…”
Section: Limitations and Future Lines Of Researchmentioning
confidence: 99%